2012
DOI: 10.1210/jc.2011-2328
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin 2 Receptor-Associated Protein (MRAP) and MRAP2 in Human Adrenocortical Tissues: Regulation of Expression and Association with ACTH Responsiveness

Abstract: MRAP and MC2R expression is induced by ACTH and AngII, which would facilitate cell surface receptor availability. Physiological expression levels of MRAP, MRAP2, and MC2R were not limiting for ACTH sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…These data suggest that MC2R and MRAP are important for adrenal gland development, and the adrenal histology of FGD supports this hypothesis as the glands from deceased patients demonstrate disorganisation of glomerulosa cells with almost complete absence of fasciculata and reticularis cells (Clark & Weber 1998). It has also been demonstrated that in vivo, mRNA levels of both MC2R and MRAP in the adrenal gland are regulated by ACTH (Xing et al 2010, Hofland et al 2012. However, at times of acute stress, the immediate steroidogenic response would depend on adequate levels of MRAP and MC2R at the surface and that can be readily trafficked to the plasma membrane.…”
Section: Melanocortin 2 Receptor Accessory Protein and Adrenal Gland mentioning
confidence: 54%
See 2 more Smart Citations
“…These data suggest that MC2R and MRAP are important for adrenal gland development, and the adrenal histology of FGD supports this hypothesis as the glands from deceased patients demonstrate disorganisation of glomerulosa cells with almost complete absence of fasciculata and reticularis cells (Clark & Weber 1998). It has also been demonstrated that in vivo, mRNA levels of both MC2R and MRAP in the adrenal gland are regulated by ACTH (Xing et al 2010, Hofland et al 2012. However, at times of acute stress, the immediate steroidogenic response would depend on adequate levels of MRAP and MC2R at the surface and that can be readily trafficked to the plasma membrane.…”
Section: Melanocortin 2 Receptor Accessory Protein and Adrenal Gland mentioning
confidence: 54%
“…Binding of ACTH to MC2R results in increase of cAMP and activation of protein kinase A, which is essential for the expression of steroidogenic enzymes and cortisol production. MC2R appears to be positively regulated by its ligand (Hofland et al 2012), and some studies have suggested a rare involvement of MC2R in adrenal cortisol-secreting tumours (Latronico et al 1995, Arnaldi et al 1998. MC2R is predominantly expressed in all zones of the adrenal cortex, but ACTH mostly acts on the zona fasciculata (Mountjoy et al 1992).…”
Section: Melanocortin 2 Receptor Is a Critical Component Of The Hpa Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Samples included normal adrenals obtained at nephrectomy because of renal cell carcinoma and hyperplastic adrenals and excised because of incurable Cushing's disease or ectopic ACTH secretion. Shortly after resection, adrenal tissue samples were dissected and primary single-layer cell cultures prepared as described previously (15). Viable lipid-laden cells were counted after isolation and plated at a density of 100,000 cells/well in DMEM-F-12 containing 5% FCS.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Hofland et al demonstrated that ACTH levels were associated with adrenal levels of MC2R in adrenal hyperplasia samples (10). Therefore, we speculated that the decreased expression of MC2R was attributable to the suppression of ACTH before surgery.…”
Section: Discussionmentioning
confidence: 84%